ANALISIS MINAT BACA SISWA SMP DI KAB. SIGI DALAM TOPIK LITERASI NUMERASI - Hajerina, Hajerina; Tangge, Lilies N.; Afadil, Afadil (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The purpose of this study was to determine students' reading interest in numeracy literacy and what factors cause students' low reading interest. This study used a quantitative descriptive method with a survey approach, namely by distributing questionnaires to a research sample of 59 students, then conducting interviews with several teachers, staff, and students. Based on the results of data analysis, it was found that the average reading interest of students in numeracy literacy was in the overall low category with an average score of 2.4, and based on the location of the school, namely in the city area, the average reading interest of students with a score of 2.4 is in the low category, in the village area the average reading interest of students with a score of 2.3 is in the low category, and in the mountainous area the average reading interest of students with a score of 2.4 is in the low category